COMPARATIVE ANALYSIS OF LEVEL THROUGH THE KNEE PROPRIOCEPTIVE FLEXIMETRY IN SEDENTARY YOUNG WOMEN PRACTITIONERS AND PHYSICAL EXERCISE (Fiep Bulletin - online, 2013)
Proprioception refers to the system's ability to capture sensory signals generated by the body of an individual, via receptors located internally in the body. The regular practice of physical exercise may be a beneficial strategy to preserve proprioception. The fleximetry is used to evaluate the flexibility and most often is also used to measure the amplitude of motion. The purpose of this study was to measure and compare the joint position sense of the knee in young sedentary women and physical exercise practitioners through fleximetry. The sample consisted of 24 women, academic in university, aged between 18 and 25 years of age without history of lower limb injury. The volunteers were divided into 2 groups of 12 people: Sedentary Group (SG) and Group Practitioner (GP). The measurement of proprioception was performed by assessing the joint position sense of the knee through fleximetry with active repositioning of the dominant lower limb after passive position  by evaluator. The analysis shows that the groups had similar performance, with the highest prevalence of error in sedentary group (SG), but without statistically significant differences. We found more satisfactory results in the group practicing, reinforcing the idea that regular exercise improves the components involved in proprioception.
Keywords: knee; proprioception; workout.